Hidden brilliance : unlocking the intelligence of autism - Koegel, Lynn Kern; LaZebnik, Claire Scovell (Harper Wave, an imprint of HarperCollinsPublishers, 2023)
"Clinician, researcher, and professor Lynn Kern Koegel, PhD, and writer Claire LaZebnik explore the ways in which the intelligence and abilities of children and young adults with autism are often overlooked and misjudged, and share interventions to bring out their full potential"--